Menjembatani Cerita Rakyat Banjar dan Bugis dengan Pendidikan Kontemporer: Nilai-Nilai Islam, Kearifan Lokal, dan Tantangan Era Digital untuk Generasi Tangguh - Irlina, Andi; Khairunnisa , Khairunnisa (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2024)
This study explores the educational values embedded in Banjarese and Buginese folklore through a qualitative comparative analysis, emphasizing local wisdom, Islamic viewpoints, language use, and contemporary educational approaches. By examining folktales from these two ethnic groups, the research highlights how their narratives reflect sociocultural and Islamic values while addressing modern challenges like technological advancements and environmental issues. Through in-depth content analysis, the study uncovers how these traditional stories impart ethical lessons, social norms, and cultural heritage, positioning them as potential tools for fostering environmental responsibility and the mindful use of technology within educational contexts. The findings suggest integrating folklore into modern curricula, especially in language teaching, to enhance cultural awareness, promote Islamic moral principles, and encourage sustainable practices. Additionally, the research underscores the relevance of folklore in nurturing essential 21st-century skills, such as critical thinking, creativity, and ethical use of technology, particularly to strengthen the generation in the digital era. The comparison highlights both the common and different aspects of local wisdom in Banjarese and Buginese folklore, providing helpful advice for teachers on how to use these stories to improve language skills, moral development, and awareness of the environment in young people. Ultimately, this study contributes to ongoing discussions about the significance of indigenous knowledge, Islamic education, and folklore's role in addressing global issues, especially in the context of the digital age.